2021
DOI: 10.21873/invivo.12385
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion Molecules in Non-melanoma Skin Cancers: A Comprehensive Review

Abstract: Basal cell carcinoma (BCC) and squamous cell carcinoma (SCC) are the most frequently diagnosed cancers, generating significant medical and financial problems. Cutaneous carcinogenesis is a very complex process characterized by genetic and molecular alterations, and mediated by various proteins and pathways. Cell adhesion molecules (CAMs) are transmembrane proteins responsible for cell-to-cell and cell-to-extracellular matrix adhesion, engaged in all steps of tumor progression. Based on their structures they ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…Together with SCC, BCC incidence is increasing worldwide, representing about 95% of the total NMSC, with a generally good prognosis, especially if recognized early [ 33 , 46 ]. Despite skin cancer pathogenesis is multifactorial, UV radiations, in particular UVB, are historically recognized to be one of the main risk factors for skin carcinogenesis [ 47 ].…”
Section: Skin Cancermentioning
confidence: 99%
“…Together with SCC, BCC incidence is increasing worldwide, representing about 95% of the total NMSC, with a generally good prognosis, especially if recognized early [ 33 , 46 ]. Despite skin cancer pathogenesis is multifactorial, UV radiations, in particular UVB, are historically recognized to be one of the main risk factors for skin carcinogenesis [ 47 ].…”
Section: Skin Cancermentioning
confidence: 99%
“…Notably, these adhesion genes are connected with angiogenesis and immune response modulation, suggesting a potential integration of broad responses. Upregulated genes included the cell adhesion molecules Icam1, Itga4, and Selp, whereas Itga2 was downregulated [54] (Figure 3B). Additionally, the transcriptome showed increased expression of the extracellular matrix proteins Wisp1, Cyr61, Lgal3bp, Nid1, Lama4, Col5a3, and Tinagl1 [55][56][57][58].…”
Section: Gene Expression Profiling Reveals a Reciprocal Regulation Of...mentioning
confidence: 99%
“…Cell adhesion in carcinogenesis is positively and negatively regulated, enabling cancer cells to attach to other cells and the extracellular matrix, favoring their permanence at the CSC niche or their migration and dissemination to distant sites [54]. The actin cytoskeleton plays a critical role in cell adhesion and migration.…”
Section: Lec-cancer Cell Adhesion Induces Reciprocal Changes In Actin...mentioning
confidence: 99%
“…At the same time, we also found that these significantly expressed functional annotations and signaling pathways have been reported in THCA and many other cancers. [27][28][29][30] At present, studies on these five hub genes have been reported, and a large number of studies have shown that their expression plays an important role in the occurrence, development and prognosis of many tumors. It has been found that SLC4A4 contributes to the occurrence and development of tumors, and its involvement in tumor biological processes is specific.…”
mentioning
confidence: 99%